Contributions to the analysis of "Integrating large scale wind power into the electricity grid in the Northeast of Brazil" [Energy 100 (2016) 401–415]. (1st January 2017) - Miranda, Raul; Soria, Rafael; Schaeffer, Roberto; Szklo, Alexandre; Saporta, Luis
Abstract: This paper contributes to the analysis made by an article recently published in this journal [1]. The purpose of this manuscript is to bring new contributions to this complex subject, namely the limits to the penetration of variable renewable energy (VRE) into national grids. A detailed and advanced model has been used in this work in order to add further contributions to De Jong et al. [1] findings. For example, by applying an optimization model, we were able to show that the high wind penetration (65%) almost without curtailment found by [1] might not happen, mainly due to inflexibility constraints in Brazilian power plants and also to transmission limits. Highlights: Wind penetration studies need to consider integration issues in a power system. Flexibility constraints and transmission limits are key factors to determine wind penetration in a power system. Wind capacity factors decrease, and wind power curtailment increases, as wind penetration increases in a power system.